2007
DOI: 10.13031/2013.22636
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Hydrologic Effects of Afforestation in the Tacuarembó River Basin, Uruguay

Abstract: The Soil and Water Assessment Tool (SWAT) was used to simulate the hydrology of two small paired catchments in northern Uruguay. The control and treatment catchments (69 and 108 ha, respectively) were monitored for a three-year pretreatment period during which the land use was grassland with livestock grazing. Subsequently, the treatment catchment was planted (57% afforested) with loblolly pine (Pinus taeda). The objectives of the modeling study were to simulate the hydrologic response of the two catchments du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 13 publications
2
12
0
1
Order By: Relevance
“…5B) periods. This same difficulty was found by other authors, such as Viola et al (2009), Pereira et al (2014a), and von Stackelberg et al (2007, and is related to the representation of the spatial and temporal rainfall distribution. The rainfall distribution in SWAT is conducted by associating the sub-basin with the nearest streamflow gauging station closest to its centroid, and because the sub-basin has only five rainfall gauging stations upstream from the control section in Astolfo Dutra, the spatial representativeness of some rainfall was compromised.…”
Section: Tablesupporting
confidence: 76%
See 2 more Smart Citations
“…5B) periods. This same difficulty was found by other authors, such as Viola et al (2009), Pereira et al (2014a), and von Stackelberg et al (2007, and is related to the representation of the spatial and temporal rainfall distribution. The rainfall distribution in SWAT is conducted by associating the sub-basin with the nearest streamflow gauging station closest to its centroid, and because the sub-basin has only five rainfall gauging stations upstream from the control section in Astolfo Dutra, the spatial representativeness of some rainfall was compromised.…”
Section: Tablesupporting
confidence: 76%
“…The years of 1994 and 1995 were used to warm up the model in order to eliminate the uncertainties existing in the beginning of modeling, particularly regarding the soil's water content (Viola et al, 2009;von Stackelberg et al, 2007;Zhang et al, 2007). The calibration was made for the average daily streamflow and was performed by trial and error by changing one parameter at a time and then analyzing the results.…”
Section: Model Calibration and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially in the case of the changed (increase/decrease) intensity of land cultivation like abandonment, reclamation, urban development and forest density (Heuvelmans et al, 2004;Schuol et al, 2008;Huang et al, 2009;Maes et al, 2009;Pisinaras et al, 2010;Bielsa et al, 2011;Dirmeyer, 2011). Different studies found strong statistical relationships between the hydrological conditions and land use change, which affects also the ecosystems (Klocking and Haberlandt, 2002;Von Stackelberg et al, 2007) and physicochemical soil properties and especially the hydraulic characteristics and processes (soil water retention capacity and surface runoff) (Eckhardt et al, 2003;Bormann et al, 2007). The results of this study also confirm the influence of a changed share of the forests in the area on the GWF (AET) (Klocking and Haberlandt, 2002;Pisinaras et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Les mesures coulometriques confirment le nombre d'electrons echanges at permettent la mise en evidence du thiomethanol produit dans la reaction. D'autre part, pour expliquer le comportement de la vague en fonction du pH, on p u t suggerer un mecanisme analogue I celui propose par M. Von Stackelberg(13) pour elucider la reduction de derives halogenes : la reaction s'effectuerait en deux Btapes, dont la premiere est lente, determine la cinetique de la reac-tion et n'inclut pas l'intervention de protons.Les variations de potentiel observees lorsque le pH de la solution varie, doivent etre attribuees a l'intense adSOrDtiOn du depolarisant et surtout des produits de reduction a la surface meme de l'electrode a goutte de mercure.L'adsorption de ces substances sur l'electrode a Bte mise en evidence anterieurement tant en polarographie conventionnelle qu'alternative ainsi qu'en voltammetrie cyclique(14).La hauteur de la premiere vague varie proportionnellement a la hauteur d e la colonne de mercure presentant ainsi un caractere se rapprochant des prevagues decrites dans les travaux de Brdicka (15,,b). En polarographie alternative (AC), le pic qui lui correspond varie peu en fonction de la f r h u e n c e mais l'epaulement resultant de l'adsorption, tres sensible aux variations de frequence, n'apparalt qu'entre 45 et 270 Hz.…”
unclassified